KNOWLEDGE SHARING TOOLS AND KNOWLEDGE TRANSFER: A MEDIATING ROLE OF MOTIVATION - Mian, Rabia; Rehman, ChaudhryAbdul; Rafiq, Muhammad; Nasir, Sobia (The journal of contemporary issues in business and government, 2021)
Knowledge sharing is an important aspect of knowledge management and it is important and progressively recognized for international business management. The aim of this study to examine the impact of knowledge sharing tools (technology and organization rewards) on knowledge transfer in the education sector of Pakistan Punjab. The survey method is used to collect the data from public and private university employees from Punjab, Pakistan. By Using the cluster random sampling method, the results of the structural equation model (SEM) and inter reliability reveals the existence of internal reliability and validity of construct with a sample of 750. Results of the research work indicate that knowledge-sharing tools organization rewards and technology have a significant impact on knowledge transfer. The results of the study also confirm that motivation mediates the relationship among organization reward, technology, and knowledge transfer. Furthermore, the organization reward and technology along with motivation endorse the knowledge transfer to individuals and organizations. This study work contributed in managerial and theatrical by considering technology and organization reward is knowledge sharing tool effect on knowledge transfer with mediation analysis of motivation which improves the organization effectiveness. The comparative study may be conducted in the future or in another region of the country.